Rheological and mechanical behavior study of eco-friendly cement mortar made with marble powder - Chahour, Kahina; Mechakra, Hamza; Safi, Brahim; Dehbi, Nacera-Melissa; Chaibet, Cylia (Zielona Góra: Uniwersytet Zielonogórski)
The work aim is to investigate the rheological and mechanical behavior of an eco-friendly mortar made with marble powder. Marble is have used as sand (total substitution of natural sand) and as an additional material (partial substitution of cement). Firstly, rheological tests were carried out on the cement pastes in order to study the effect of cement substitution by marble powder on the rheological behavior. Secondly, our study is devoted to evaluate the mechanical performances (flexural strength, compressive strength, mechanical behavior and ultrasonic pulse velocity) of a fluid mortar such as the case of the self-compacting mortars elaborated with the marble powder as an addition a material and as sand.
Keywords: powder marble wastes; mortar; sand; rheological properties; viscosity; mechanical strength; mechanical behavior and strength gain